2018
DOI: 10.1017/s0144686x18001307
|View full text |Cite
|
Sign up to set email alerts
|

Age management in the workplace: manager and older worker accounts of policy and practice

Abstract: The impact of an ageing workforce on the workplace is a concern internationally. Governments are increasingly encouraging the continued labour market participation of older workers, seeking to remove previous barriers to the extension of working lives and give more choice to workers. Despite these legislative drivers, research has consistently found a lack of systematic approaches by employers to prepare and benefit from these demographic and labour market changes. In this paper, qualitative research is drawn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 52 publications
4
59
0
6
Order By: Relevance
“…everal researchers have concluded that older workers' opportunities for late careers, and the restrictions they potentially face, are to a large degree shaped by their employers' attitudes and willingness to retain older staff, and to hire older workers (Egdell et al 2018;Hermansen 2016, p. 29). According to Henkens and van Dalen, employers are 'key players in defining the opportunities for retirement as well as the opportunities for working longer ' (2012, p. 25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…everal researchers have concluded that older workers' opportunities for late careers, and the restrictions they potentially face, are to a large degree shaped by their employers' attitudes and willingness to retain older staff, and to hire older workers (Egdell et al 2018;Hermansen 2016, p. 29). According to Henkens and van Dalen, employers are 'key players in defining the opportunities for retirement as well as the opportunities for working longer ' (2012, p. 25).…”
mentioning
confidence: 99%
“…Several scholars relate this reluctance among employers to concepts such as 'stereotypes', 'age discrimination' or 'ageism' (Ayalon & Tesch-Römer 2017;Egdell et al 2018;Furunes & Mykletun 2011;Henkens 2010;Kadefors & Hanse 2012;Kroon et al 2018). 'Age stereotyping' has been defined as 'a simplified, undifferentiated portrayal of an age group that is often erroneous, unrepresentative of reality, and resistant to modification' (Chiesa et al 2016(Chiesa et al , p. 1153Schulz 2006) and is often referred to as part of the wider concept of 'ageism'.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the absence of formal plans to manage the workplace for older workers led managers to assess work capacity on an individual basis (Egdell et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is helpful when awareness about the younger leaders' weaknesses addresses the challenges, in order to train new managers (Zenger and Folkman, 2015). Finally, the employees' age and fitness for work is treated on an individual basis, rather than having formal plans to manage the workplace for older workers, but not a plan from the management (Egdell, 2018).…”
Section: Management and Age Of The Participantsmentioning
confidence: 99%